A presença de Aristóteles no livro Como pensamos, de John Dewey - Cunha, Marcus Vinicius Da [UNESP]; Ribeiro, Aparecida Pin; Rassi, Nicole (Faculdade de Educação da Universidade Federal de Minas Gerais, 2007)
This article is part of a research project whose goal is discussing occasional relations between John Dewey's thesis and the classical Greek philosophy, especially concerning the notion of knowledge or science. We intend to understand the mechanisms behind the appropriation and re-contextualization in Pedagogical discourses. In order to do so, we analyzed the book How we think, in which the fundamentals of Dewey's logical theory can be seen, proceeding to an interpretation of his ideas based on Aristotle's. Our conclusion points to some similarities and distinctions between the two philosophers' conceptions, allowing us to raise some new hypothesis for further studies about relations between Dewey and Aristotle.

Este artigo integra um projeto de pesquisa que tem por objetivo discutir eventuais relações entre as teses de John Dewey e a filosofia grega clássica, especialmente em torno da noção de conhecimento ou ciência, no intuito de compreender os mecanismos de apropriação e recontextualização presentes na elaboração de discursos pedagógicos. Para isso, analisamos o livro Como pensamos, em que se encontram os fundamentos da teoria lógica deweyana, procedendo a uma interpretação das idéias do autor à luz do pensamento de Aristóteles. As conclusões indicam haver certas aproximações e diferenças entre as concepções dos dois filósofos, o que permite formular algumas hipóteses para novos estudos acerca das relações entre Dewey e Aristóteles.
The presence of Aristotle in the book How we think by John Dewey
Keywords: John Dewey; Pedagogical Discourse; Aristotle; Thinking; John Dewey; Discurso pedagógico; Aristóteles; Pensamento